How Does AI Enable Remote Cardiac Monitoring? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Remote cardiac monitoring is rapidly transforming cardiovascular care, allowing for the continuous tracking of patients' heart health outside of traditional ...
Keywords: AI in Cardiology; Enable; Remote; Cardiac; Artificial Intelligence; Machine Learning; Healthcare